Power moments of negative order for the principal spectral function of a string - Kats, I. S. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We established necessary and sufficient conditions for the existence of finite power moments of all integer negative orders for the principal spectral function of a string. The necesity of this problem is explained by its relation to the so-called strong Stieltjes moment problem.